Non-Destructive X-ray Spectrometric and Chromatographic Analysis of Metal Containers and Their Contents, from Ancient Macedonia - Christos S. Katsifas; Despina Ignatiadou; Anastasia Zacharopoulou; Nikolaos Kantiranis; Ioannis Karapanagiotis; George A. Zachariadis (Separations, 2018)
This work describes a holistic archaeometric approach to ancient Macedonian specimens. In the region of the ancient city Lete, the deceased members of a rich and important family were interred in a cluster of seven tombs (4th century BC). Among the numerous grave goods, there was also a set of metal containers preserving their original content. The physico-chemical analysis of the containers and their contents was performed in order to understand the purpose of their use. For the containers, Energy Dispersive micro-X-Ray Fluorescence (EDμXRF) spectroscopy was implemented taking advantage of its non-invasive character. The case (B35) and the small pyxis (B37) were made of a binary Cu-Sn alloy accompanied by a slight amount of impurities (Fe, Pb, As) and the two miniature bowls were made of almost pure Cu. For the study of the contents, a combination of EDμXRF, X-Ray Diffraction (XRD), and Gas Chromatography—Mass Spectrometry (GC-MS) was carried out. Especially for the extraction of the volatile compounds, the Solid Phase Micro-Extraction (SPME) technique was used in the headspace mode. Because of the detection of Br, High Pressure Liquid Chromatography coupled to a Diode-Array-Detector (HPLC-DAD) was implemented, confirming the existence of the ancient dye shellfish purple (porphyra in Greek). The analytical results of the combined implementation of spectrometric and chromatographic analytical techniques of the metal containers and their contents expand our knowledge about the pharmaceutical practices in Macedonia during the 4th century BC.